Características físico-química e microbiológica e aminas bioativas em ovos de consumo - Tadeu Chaves de Figueiredo (2008)
Physical-chemical and microbiological qualities of commercial eggs produced by layer hens of different ages (approximately 30 and 60-week-old) and were submitted to storage under room temperature or refrigeration conditions and two experiments were carried out. In the first, 1440 eggs were used and their inner quality was daily evaluated, from one to 15 days of storage, according to the following parameters: albumen height (AA); Haugh Unities (UH); pH of albumen (pH); total solids of albumen and yolk; and weight and percentage of albumen, yolk, and shell. In the second, which lasted 28 days, 600 eggs were used for microbiological analyses of their inner content and other 600 to the determinations of AA, HU, and contents of bioactive amines. Decrease of inner quality of the evaluated eggs was observed during the experiment, mainly eggs from old-layers, which presented the worst values of AA and HU when stored at room temperature. Microbiological analyses showed absence of Salmonella spp.; Staphylococcus aureus; and coliforms either total or termotolerants; however, other Staphylococcus species, Enterobacter spp., and Pseudomonas spp. were found. Besides, mesophilic aerobic and fungi were also isolated